Beberapa Faktor Kejadian Perdarahan Postpartum Ibu Bersalin yang Dirawat Di Rumah Sakit - Asif Yuliati; Ariawan Soejoenoes; Ari Suwondo; Anies Anies; Martha Irene Kartasurya (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2018)
Background: Postpartum hemorrhage (PPH) remains a leading cause of maternal morbidity and mortality in both developed and developing countries. To prevent postpartum hemorrhage, knowledge of the risk factors were needed.Method: Methos of the research is a case control study. Study population were hospitalized mothers who delivered in three hospitals on January 2015 – July 2016. The subjects were 55 patients who suffered from PPH (as cases) and 55 patients who were not suffered from PPH (as control). Sampling method for cases was consecutive sampling and purposive for controls. Data were analysed by Odds Ratio calculation and logistic regression.Results: The risks factor significantly for PPH are midwife as birth attendant (OR=7.10; 95% CI 2.2 –22.81; p=0.001), poor of obstetric history (OR=5.37; 95%CI 1.53–18.86; p=0.009), pregnancy interval (< 2 years or > 5 years) (OR =4.04; 95%CI 1.48 –11.07; p= 0,007), anaemia trimester III (OR =3,58; 95%CI 1.23-10.43; p=0.019), history of abortion (OR=4.93; 95% CI 1.20-20.31; p=0,027).Conclusion: The risk factors for PPH were midwife as birth attendant, poor of obstetric history, pregnancy interval (<2 years and >5 years), anaemia trimester III, and history of abortion.